Dual Specificity Phosphatase 5 Is Essential for T Cell Survival. - Raman G Kutty; Gang Xin; David M Schauder; Stephanie M Cossette; Michelle Bordas; Weiguo Cui; Ramani Ramchandran (PLoS ONE, 2016)
The mitogen-activated protein kinase (MAPK) pathway regulates many key cellular processes such as differentiation, apoptosis, and survival. The final proteins in this pathway, ERK1/2, are regulated by dual specificity phosphatase 5 (DUSP5). DUSP5 is a nuclear, inducible phosphatase with high affinity and fidelity for ERK1/2. By regulating the final step in the MAPK signaling cascade, DUSP5 exerts strong regulatory control over a central cellular pathway. Like other DUSPs, DUSP5 plays an important role in immune function. In this study, we have utilized new knockout mouse reagents to explore its function further. We demonstrate that global loss of DUSP5 does not result in any gross phenotypic changes. However, loss of DUSP5 affects memory/effector CD8+ T cell populations in response to acute viral infection. Specifically, Dusp5-/- mice have decreased proportions of short-lived effector cells (SLECs) and increased proportions of memory precursor effector cells (MPECs) in response to infection. Further, we show that this phenotype is T cell intrinsic; a bone marrow chimera model restricting loss of DUSP5 to the CD8+ T cell compartment displays a similar phenotype. Dusp5-/- T cells also display increased proliferation, increased apoptosis, and altered metabolic profiles, suggesting that DUSP5 is a pro-survival protein in T cells.